Clinical Characteristics of Myelin Oligodendrocyte Glycoprotein Antibody Neuromyelitis Optica Spectrum Disorder. - Salama, Sara (Mult Scler Relat Disord, 2019)
BACKGROUND. Serological antibodies against myelin oligodendrocyte glycoprotein (MOG) are associated with a relapsing autoimmune demyelinating disease of the central nervous system. Initially identified in the context of acute disseminated encephalomyelitis, persistent seropositivity of MOG antibodies is now recognized as a variant of neuromyelitis optica spectrum disorder (NMOSD). OBJECTIVES: The aim of the study is to describe the epidemiological and clinical features of MOG antibody positive cases and compare our findings with those previously published. METHODS. This is a retrospective descriptive study of 23 patients with MOG antibody disease who were cared for at Johns Hopkins Hospital over the period from 2015 to 2018. MOG testing was done at Johns Hopkins using the cell based assay (CBA). We describe their epidemiological and clinical features. RESULTS. Twenty-three patients were included in the study with a female to male ratio of 2.3:1. The mean age of the cohort was 42.6 years, while the mean age at onset was 37 years. The most frequent initial presentation was optic neuritis, followed by ADEM-like encephalopathic clinical picture and transverse myelitis. Five patients showed a monophasic disease course while the rest experienced a relapsing phenotype. Nine patients (39%) experienced immediate relapses on withdrawal of steroids. CONCLUSIONS. Our cohort showed clinical characteristics comparable with previously published reports of MOG antibody disease worldwide. Unique features of MOG antibody disease are: high frequency of optic neuritis attacks, good long term neurological recovery and sensitivity to steroid use and withdrawal.